Forming the competence of future bachelors of agroengineering under the domestic agriculture modernisation - Domin, Alexander (Professional Pedagogics, 2018)
The article touches upon the problem which had been almost ignored by pedagogical society in independent Ukraine for a long time. The problem is that formation of professional competencies of bachelors of agro-engeneering must adapt to basic changes in native agriculture, which had occurred since Ukraine became independent. During this time, as a result of deep reforms, the forms of ownership changed from communal and state ones to private in agriculture. Therefore modern private agricultural companies run their business and develop according to strict laws of market economy. It means that the main goal of this type of management is the biggest profit above all. Due to such not very progressive development the following changes in professional training of engineering specialists for established for decades agricultural sphere took place: breaking the ties between private agricultural companies and higher educational institutions of agricultural profile, violation of the necessary conditions for soil fertility restoration, efficiency gain at the expense of highly qualified personnel that leads to transmission of agronomics, agrochemical services, plant protection and others activity problems into the charge of bachelors of agro-engineering; higher priority ranking of imported agricultural techniques, that leads Ukrainian agriculture to total dependence on foreign producers of expandable materials, fuel and lubricants for these technics. This list can be extended, but in our opinion, the number of above-mentioned changes is enough to understand that a significant problem exists in formation of professional competencies of future agroengineering bachelors according to not perfectly studied requirements of modern native agriculture.